Investment funds under stress - Régis Gourdel; Eduardo Maqui; Matthias Sydow (European Central Bank (ECB), 2019)
This paper presents a model for stress testing investment funds, based on a broad worldwide sample of primary open-end equity and bond funds. First, we employ a Bayesian technique to project the impact of macro-financial scenarios on country-level portfolio flows worldwide that are constructed from fund-level asset holdings. Second, from these projected countrylevel flows, we model the scenarios' repercussions on individual funds along a three year horizon. Importantly, we further decompose portfolio flows, disentangling the specific contributions of transactions, valuation and foreign exchange effects. Overall, our results indicate that the impact of a global adverse macro-financial scenario leads to a median depletion in assets under management (AUM) of 24% and 5%, for euro area-domiciled equity and bond funds respectively, largely driven by valuation effects. Scenario and results both present similarities to the global financial crisis. We use historical information on fund liquidations to estimate a threshold for a drop in AUM that signals a high likelihood of a forthcoming liquidation. Based on this, we estimate that 5.8% and 0.5% of euro area-domiciled equity and bond funds respectively could go into liquidation. Such empirical thresholds can be useful for the implementation of prudential policy tools, such as redemption gates.
Keywords: F21; G15; G17; G23; G28; 330; Investment funds; Bayesian model averaging; international capital flows; portfoliovaluation; prudential policy